Gambaran tingkat aspirasi karir siswa sekolah menengah atas - Alif Nahdatul Akbar; Hamzah Hamzah (Universitas Indraprasta PGRI, 2022)
career aspiration is one of the career competencies that students need to have. Career aspirations need to be developed optimally in students. The aim of this study was to find out how the description of the career aspirations of students. This research is a quantitative research with descriptive type. The population in this study amounted to 1,219 students. Samples were drawn randomly with a degree of error of 0.1. Through the Slovin formula, it is known that the sample size is 92 students. Career aspirations in this study were measured using a career aspiration scale. Data were analyzed descriptively. The results showed that the level of students' career aspirations was in the medium category. These results need to be followed up by providing counseling services in order to minimize the long-term effects that will arise if career aspirations do not run optimally